The second complete chloroplast genome of Dysphania pumilio (R.Br.) mosyakin & clemants (Amranthaceae): intraspecies variation of invasive weeds - Jongsun Park; Yongsung Kim (Mitochondrial DNA. Part B. Resources, 2019)
We completed chloroplast genome of Dysphania pumilio (R.Br.) Mosyakin & Clemants isolated in Anyang city in Korea. Its length is 151,960 bp consisting four subregions: 83,756 bp of large single copy (LSC) and 17,742 bp of small single copy (SSC) regions are separated by 25,231 bp of inverted repeat (IR) region. 128 genes (84 protein-coding genes, eight rRNAs, and 36 tRNAs) were annotated. The overall GC content is 36.9% and those in LSC, SSC, and IR regions are 34.8%, 30.4%, and 42.7%, respectively. 25 single nucleotide polymorphisms and two insertions and deletions suggest multiple invasive origins in Korea.